(untitled) (Práxis Educativa, 2014)
The purpose of this article is to contextualize the political expansion of places in Higher Education undertaken by the last governments of the Brazilian State in the Reform of Higher Education in a time frame referring to the last two decades of the last century and that is still in the process of implementation. With this goal, it will be questioned: what were the impacts of these policies on Higher Education? When and how are these projects historically situated in this process? The methodological approach aimed to analyze, based on this theoretical issue, if the data published by INEP in Higher Education Censo reflect the discourse of democratization of access to this level of education. We took into account the current Brazilian Higher Education, the recent political-economic context of globalized economy, the redefinition of the role of the nation state and its relationship with civil society, its different performance fronts and areas of interest. Keywords: Education Policy. Higher Education. Higher Education Censo.